Análise espacial do risco de fasciolose bovina no estado do Espírito Santo por meio dos sistemas de informações geográficas - Freitas, Deivid França (2013)
The fasciolosis is a disease that affects domestic and wild ruminants and eventually the man. By causing great economic losses to cattle ranching and the high power of global dissemination, it sought alternatives to facilitate the understanding and visualization of disease delimiting potential risk areas in the Espírito Santo state. Thus, favorability maps were drawn on the current and future risk to F. hepatica based on climatic and environmental variables considered essential for maintenance of the disease and bioclimatological zoning maps and prevalence through the Geographic Information System (GIS). The data of cattle slaughter in the Espírito Santo were collected from the 11 slaughterhouses supervised by federal and state inspection services (SIF/SIE/MAPA), beyond the origins of livestock slaughtering in a slaughterhouse located in the municipality of Anchieta in the years 2009 to 2011. So, mapping results showed that areas of high risk gaskets totaled 35.42% for the current risk and tended to lessen with increases of 1°C to 5°C in temperature for 33.84%. The zoning map showed that 52.24% of the state areas are located in zones considered suitable for disease development. The combination of maps generated by zoning and prevalence of the 11 slaughterhouses distributed in the state showed that the highest prevalence rates were found in the municipalities located in the Southern region with averages ranging from 0.01% to 28.41%. Considering the result became clear that the epidemiological data, combined with GIS become a valuable tool for making decisions in order to minimize the occurrence and prioritize strategies for prevention and control of fasciolosis in Espirito Santo